Soft Computing: State of the Art Theory and Novel Applications - Yager, Ronald R.; Abbasov, Ali M.; Reformat, Marek Z.; Shahbazova, Shahnaz N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is a tribute to Lotfi A. Zadeh, the father of fuzzy logic, on the occasion of his 90th Birthday. The book gathers original scientific contributions written by top scientists and presenting the latest theories, applications and new trends in the fascinating and challenging field of soft computing.
From the Contents: Future Novel Directions -- Fuzzy Sets and Relations -- Rules Construction and Analysis -- Learning and Databases -- Fuzzy Logic -- Data Analysis and Applications.
Keywords: Engineering; Artificial intelligence; Computer science; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Computer Applications